Capacity building on agricultural insurance for aggregators in Northern Ghana - Greatrex, Helen; Narh, Stephen; Tettey, Abigail; Yeboah, Angelina; Mahama, Aswad (2017)
Farming is a risky business. Shocks such as drought, flood, pests or disease can make it difficult for farmers to invest in new productive options, such as seeds or fertilizer. These shocks are often regional, reverberating past the level of the individual smallholder. This makes it equally difficult for aggregators such as seed companies, input providers, agri-shops, seed growers and for commercial farmers, all of whom rely on the yields of a large number of smallholders or out-growers. Agricultural insurance is one way to mitigate this risk, unlocking new markets and making existing markets more profitable Most training on insurance is either designed for poor smallholder farmers, or for very large aggregators (e.g. a country-wide fertilizer company). Less attention has been paid to small and medium level aggregators, who might have tens or hundreds of acres, or have a relationship with a smaller number of out growers (tens to thousands). However, connecting with these stakeholders is one method of scaling insurance in a sustainable fashion. The local nature of many of the aggregators allows insurance to reach smallholders without personally visiting every village. The aggregators are also typically from the local communities and can act as champions for new initiatives. These same incentives for connecting with aggregators also hold true for other CCAFS and rural development initiatives. The aim of this workshop was to reach a group of local aggregators in rural Ghana with tailored insurance capacity building material, detailed in this report. A secondary aim was to gather their feedback about their experiences with agricultural insurance, along with jointly designed ideas about how insurance could more easily fit in with their practices.